Ep7GT, a glycosyltransferase with sugar donor flexibility from Epimedium pseudowushanense, catalyzes the 7-O-glycosylation of baohuoside. Issue 35 (28th August 2019) - Feng, Keping; Chen, Ridao; Xie, Kebo; Chen, Dawei; Liu, Jimei; Du, Wenyu; Yang, Lin; Dai, Jungui
Abstract : A novel glycosyltransferase from Epimedium pseudowushanense, Ep7GT, regiospecifically catalyzes the 7- O -glucosylation of baohuoside to form icariin and shows sugar donor/acceptor promiscuity to yield different flavonoid glycosides. Abstract : Icariin (1a ), a 7- O -glycosylated flavonoid glycoside, is recognized as the major pharmacologically active ingredient of Epimedium plants, which have been used in traditional Chinese medicine for thousands of years. However, no glycosyltransferase (GT) responsible for the 7- O -glycosylation of flavonoids has been identified from Epimedium plants to date. Herein, a GT, Ep7GT, was identified from E. pseudowushanense B. L. Guo, which can regiospecifically transfer a glucose moiety to baohuoside (1 ) at 7-OH to form icariin (1a ). Ep7GT showed a rare broad donor substrate spectrum, including UDP-glucose, UDP-xylose, UDP- N -acetylglucosamine, UDP-rhamnose, UDP-galactose, UDP-glucuronic acid and TDP-glucose. Moreover, two new derivatives of icariin (1a ), 7- O -β-d -[2-(acetylamino)-2-deoxy-glucopyranosyl]-baohuoside (1b ) and 7- O -β-d -xylosyl-baohuoside (1c ), were biosynthesized by using Ep7GT in vitro . Engineered Escherichia coli harbouring Ep7GT was constructed, and 10.1 μg mL −1 icariin (1a ) was yielded by whole-cell biotransformation with baohuoside (1 ) as the substrate. The present work not only characterizes the GT responsible for the 7- O -glycosylation in the biosynthesis of icariin in Epimedium plants, but also indicates the significant potential of an enzymatic approach for the production of glycosylated baohuoside derivatives with different sugar moieties. What's more, these findings also provide a promising alternative for producing natural/unnatural bioactive flavonoid glycosides by metabolic engineering.